The Greek Life of St. Leo Bishop of Catania (BHG 981b). Text and notes by A. G. Alexakis - Smith, Jennifer Nimmo (The journal of theological studies, 2012)
The Greek and Latin Lives of St Leo, Bishop of Catania (BHG 981) have long stirred both interest and discussion. The Société des Bollandistes is to be congratulated on its vision in clarifying the debate with this new edition (with a full introduction, translation, and commentary) of the longer version of the Greek Life (BHG 981b) by Professor Alexakis., Leo of Catania, a saint and bishop, came originally from Ravenna. His Life, described by A. Kazhdan as a ‘unique text in Byzantine hagiography’ (ODB, s.n.), tells of his defeat of a colourful and inventive local magician, Heliodorus, after much discussion of the latter’s exploits not only in Sicily but also in Constantinople.